1998
DOI: 10.1046/j.1365-3156.1998.00322.x
|View full text |Cite
|
Sign up to set email alerts
|

Survey among survivors of the 1995 Ebola epidemic in Kikwit, Democratic Republic of Congo: their feelings and experiences

Abstract: SummaryThis study describes experiences of the survivors of the 1995 Ebola epidemic in Kikwit, Democratic Republic of Congo. Most of the survivors in our sample had cared for a sick family member before becoming ill themselves, and most had never heard of Ebola before they developed symptoms and therefore did not suspect that they were infected by the virus. Fear, denial and shame were their principal initial feelings. After release from hospital, survivors were abandoned by family or friends more often than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 5 publications
2
85
0
Order By: Relevance
“…15 Survivors and orphans of those who died from the disease face stigma and ostracism in many communities. This-along with substantial associated psychological disturbance-was reported after previous outbreaks, 83 84 and it is an increasing problem in the 2014 outbreak.…”
Section: What Advice Should Patients Be Given During Recovery?mentioning
confidence: 76%
“…15 Survivors and orphans of those who died from the disease face stigma and ostracism in many communities. This-along with substantial associated psychological disturbance-was reported after previous outbreaks, 83 84 and it is an increasing problem in the 2014 outbreak.…”
Section: What Advice Should Patients Be Given During Recovery?mentioning
confidence: 76%
“…5−13 Disabling sequelae, including ocular, auditory, and arthritic symptoms, have been described in small studies from previous outbreaks. 7,[9][10][11]13 In the current outbreak, one qualitative study of 100 survivors in Sierra Leone reported blurred or partial loss of vision in convalescence but did not quantify these sequelae. 2 Surveys of 105 survivors in Guinea 14 and of 81 survivors in Sierra Leone 15 noted frequent musculoskeletal pain 14,15 and visual problems; 15 neither study included a clinical examination of survey participants.…”
Section: Introductionmentioning
confidence: 94%
“…Survivors frequently encountered stigma, rejection, and shunning at the hands of their own family members and neighbors [8, 24•, 29••, 77, 78]. As Rabelo et al summarized, “when EVD survivors returned home, the experience of being alive was both a gift and a burden” [29••].…”
Section: Fear-related Behaviors In the 2013–2106 Evd Outbreakmentioning
confidence: 99%